"Game Changer": Health Professionals' Views on the Clinical Utility of Circulating Tumor DNA Testing in Hereditary Cancer Syndrome Management. (6th April 2022) - Shickh, Salma; Oldfield, Leslie E; Clausen, Marc; Mighton, Chloe; Sebastian, Agnes; Calvo, Alessia; Baxter, Nancy N; Dawson, Lesa; Penney, Lynette S; Foulkes, William; Basik, Mark; Sun, Sophie; et al.
Abstract : This article reports on health professionals' views on the utility of circulating tumor DNA testing in hereditary cancer syndrome management. Abstract: Background: We explored health professionals' views on the utility of circulating tumor DNA (ctDNA) testing in hereditary cancer syndrome (HCS) management. Materials and Methods: A qualitative interpretive description study was conducted, using semi-structured interviews with professionals across Canada. Thematic analysis employing constant comparison was used for analysis. 2 investigators coded each transcript. Differences were reconciled through discussion and the codebook was modified as new codes and themes emerged from the data. Results: Thirty-five professionals participated and included genetic counselors ( n = 12), geneticists ( n = 9), oncologists ( n = 4), family doctors ( n = 3), lab directors and scientists ( n = 3), a health-system decision maker, a surgeon, a pathologist, and a nurse. Professionals described ctDNA as "transformative" and a "game-changer". However, they were divided on its use in HCS management, with some being optimistic (optimists) while others were hesitant (pessimists). Differences were driven by views on 3 factors: (1) clinical utility, (2) ctDNA's role in cancer screening, and (3) ctDNA's invasiveness. Optimists anticipated ctDNA testing would have clinical utility for HCS patients, its role would be akin to a diagnostic test and would be less invasive than standard screening (eg imaging). Pessimistic participants felt ctDNA testing would add limited utility; it would effectively be another screening test in the pathway, likely triggering additional investigations downstream, thereby increasing invasiveness. Conclusions: Providers anticipated ctDNA testing will transform early cancer detection for HCS families. However, the contrasting positions on ctDNA's role in the care pathway raise potential practice variations, highlighting a need to develop evidence to support clinical implementation and guidelines to standardize adoption.